Tulaberry Plaza : leasing decisions in commercial real estate - Furfine, Craig (SAGE Business Cases., 2019)
In January 2019, Benedict Clarke needed to address the vacancies at retail shopping center Tulaberry Plaza in Southeast Orlando. The rise in online shopping forced Tulaberry's anchor tenant into bankruptcy and weakened the outlook for retail more generally. Clarke must devise a plan that presents the most logical and profitable way forward for the shopping center. The case asks students to make leasing decisions from the perspective of the property owner, Clarke, giving them an appreciation for both the quantitative and qualitative factors that influence optimal leasing decisions.